The Use of Husserl’s Method in Bernard Lonergan’s Trinitarian Theology - Baba, Teodor Bernardus (Philosophy & theology, 2009)
The question that arises in this article is whether we can find elements of phenomenology in Bernard Lonergan’s Trinitarian theology. With help of other Lonergan scholars, I have discovered that modern thinking plays an important role in the theology and philosophy of this Jesuit author. Moreover, the terminology of modern philosophy coexists with the terminology of classical and especially Tomistic thought. This article is interested in the elements that Lonergan takes from the modern philosophy and emphasizes the centrality of Husserlian phenomenology among the other modern authors used by Lonergan. Following the research of the Jesuit thinker, I speak about two parallel realities coexisting in his Trinitarian theology. Lonergan tries to realize their synthesis, but at the same time he also recognizes their distinctiveness. The most relevant result of this coexistence is obtained through the replacement of the metaphysical differentiation between the level of substance and the level of the three Persons, so that, instead of having the elements of classical theology, Lonergan predicates at the same time that God subsists as well as the Trinitarian Persons subsist. Through this assertion he emphasizes the identity between God’s existence and the existence of the three divine Persons, and eliminates the classical differentiation that might be closer to the danger of subordinating the three Persons to the one God.